Terrestrial, space and lunar human isolation: Comparison of proxemics dimensions and other isolation stressors from coronavirus to space - Schlacht I. L.; Masali M.; Pregnolato Rotta Loria F. F.; Micheletti Cremasco M.; Foing B. (International Astronautical Federation (IAF), 2020)
From isolation of people in case of an epidemic (such as Coronavirus), refugees, mineworkers, clochards, convicts, monks, feral children, isolated tribes, scientists in Antarctic settlements or in Outer Space; life in isolation is a condition that affects more people every day. Isolation is an element which strongly affects human behavior, interpersonal relationships, mood and cognitive performances. It may create stress and social conflict, which, because of the isolation, need to be managed mostly independently. Specifically in Space the independence and reliability of the astronauts is fundamental for the overall survival of the crew. Isolation may perhaps be cultural, forced, voluntary, dimensional, temporal, and environmental; however isolation in Space is one of the most extreme forms that have ever been experienced by humans. In this paper the intent is to compare the different factors (such as Proxemics) which characterize different modes of isolation as a source for future foresight and problem solving in the Space context, such as future Moon and Mars settlements and spin off applications. For instance, one focus of interest is on the Proxemics: the "Science of proximity" proposed in the 1960s by Edward T. Hall as a fundamental expression of interpersonal perceptions of body dimensions and interpersonal distances (the so called "Hidden Dimension"), and towards built and technological surroundings (our proposed concept of "Interspace").